Lignin Sulfonate-Chelated Calcium Improves Tomato Plant Development and Fruit Quality by Promoting Ca2+ Uptake and Transport - Jiucheng Zhang; Minghui Du; Genzhong Liu; Fangfang Ma; Zhilong Bao (Horticulturae)
Calcium (Ca) plays a key role in cell wall stabilization and various physiological processes. Ca fertilizers are widely used in agriculture to meet crop demands and improve yield and quality. However, traditional Ca fertilizers often suffer from low solubility, poor absorption, and mobility issues. Chelated Ca fertilizers offer enhanced efficiency and uptake. In this study, we compared the effects of lignosulfonate-chelated Ca (LS–Ca), EDTA-chelated Ca (EDTA–Ca), Ca(NO3)2, and alcohol sugar-chelated Ca (AS–Ca) with a Ca concentration of 15 mg/L on tomato growth. The results showed that LS–Ca increased the contents of chlorophyll a and b contents in leaves by 26% and 46%, respectively. The application of Ca fertilizers significantly enhanced Ca2+ uptake and transport, with the LS–Ca treatment achieving the highest utilization efficiency. Without altering fruit weight, the LS–Ca treatment increased the firmness of mature tomato fruits by 29%. Furthermore, the LS–Ca treatment improved fruit sweetness by 33%, with the total sugar content increasing by 45%, sucrose by 80%, reducing sugars by 64%, and titratable acidity by 18%. This study aims to compare the effects of different chelated Ca fertilizers on tomato cultivation and to explore optimal Ca supplementation strategies, thereby contributing to improvements in tomato cultivation practices and fruit quality.